2010
DOI: 10.4269/ajtmh.2010.09-0660
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks and Travel Preparation Among Foreign Visitors and Expatriates During the 2008 Beijing Olympic and Paralympic Games

Abstract: Abstract. During the 2008 Olympic and Paralympic Games, we conducted surveillance of illnesses among travelers at six Beijing clinics. Surveys asked about demographic, pre-travel, and vaccination information, and physician-provided diagnoses. Of 807 respondents, 38% and 57% were classified as foreign visitors (FV) and expatriates, respectively. Less than one-half of FV sought pre-travel advice; sources included health-care providers and friends/family. FV vaccination rate was also low; however, most vaccines g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Travel restricted to World Cup venues will have a different risk profile to the 30% (based on usual experience) who also visit more rural areas in neighboring countries. Interestingly, studies of travelers to Beijing before 23 and during 24 the 2008 Olympics showed that both suffered predominantly from respiratory illnesses, suggesting some overlap between "normal" international travelers and those that attend a mass gathering in the same country.…”
mentioning
confidence: 99%
“…Travel restricted to World Cup venues will have a different risk profile to the 30% (based on usual experience) who also visit more rural areas in neighboring countries. Interestingly, studies of travelers to Beijing before 23 and during 24 the 2008 Olympics showed that both suffered predominantly from respiratory illnesses, suggesting some overlap between "normal" international travelers and those that attend a mass gathering in the same country.…”
mentioning
confidence: 99%
“…In the 2006 winter Olympics in Torino, Italy, surveillance for acute gastroenteritis, influenza-like illnesses, measles, and other infections found incidences similar to non-Olympics time periods [14]. Similar experiences were reported in the earlier Summer Olympics in Atlanta (1996) and Los Angeles (1984) [10]. However, epidemiological alerts can happen, as shown by an anthrax alert at the Salt Lake City airport on the first night of the 2002 Winter Olympics, which was found to be due to an environmental sample that falsely tested positive [15].…”
Section: Introductionmentioning
confidence: 70%
“…Influenza outbreaks have been reported in settings of varying scale, ranging from outbreaks in close living conditions (including troop ships [5] and airplanes [6,7]) to outbreaks in large public gatherings (such as the Winter Olympics in 2002 in Salt Lake City, USA[8] and the World Youth Day in July 2008 in Sydney [9]). Further, respiratory illness was the most common diagnosis made at a surveillance clinic during the 2008 Olympic and Paralympic Games held in Beijing and other cities of China [10]. More recently, increased 2009 pandemic influenza virus activity has been reported during several music festivals [11], and the pandemic transmission risk at the 2009 Hajj pilgrimage and the Asian South Games was deemed sufficiently important to prompt a strengthening disease surveillance systems and implementation of vaccination programs [2,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk behavior with respect to sexual contacts may be gender-or destination specific: While travelers to the FIFA world cup 2014 in Brazil had a higher rate of condom carriage, which was independently associated with alcohol consumption, and reported a significantly higher rate of sexual contacts outside of a relationship or the need for HIV testing after return, studies on STDs during the Olympic Games in London 2012 did not show increased attendances at sexual health services [37,38]. An explanation might be that football traditionally attracts more male fans than the Olympic Games, also shown by the gender distribution of clinical consultations during the 2008 Summer Olympic Games in Beijing [39]. Another reason for higher rates of alcohol use and sexual contacts outside of a relationship in our case group may be explained by psychological aspects of specific MGs.…”
Section: Discussionmentioning
confidence: 86%